What's Hot in Clinical Infectious Diseases? 2019 IDWeek Summary. (23rd March 2020) - Moss, Sean; Boucher, Helen W
Abstract: The year 2019 brought about a multitude of innovations in clinical infectious diseases. With the continued rise of antimicrobial resistance (AMR), advances in diagnostics and newly available antibiotics offer additional strategies for combating this threat, but the broken antibiotic market serves as an impediment to further developments. The IDSA and other stakeholders are working to create novel pull incentives to stabilize the pipeline. Ongoing needs include developing optimal stewardship practices, including by using narrow-spectrum antibiotics and shorter durations of therapy. In the area of solid organ transplantation, early data from transplanting Hepatitis C virus (HCV)-infected organs are encouraging and the American Society of Transplantation (AST) released new guidelines addressing several key issues. Lastly, 2019 saw a resurgence in Measles emphasizing the importance of vaccination. Abstract : In 2019, there were numerous new developments in clinical infectious diseases. We discuss strategies for combatting the ever-evolving threat of antimicrobial resistance, updates in solid organ transplantation guidelines, as well as the resurgence of measles.